The Internationalization of the Academic Library - Lombard, Emmett (Routledge Studies in Library and Information Science, 2021)
The Internationalization of the Academic Library presents a theoretically informed, empirically grounded analysis of the process of academic library internationalization. Drawing on interviews with library personnel from around the world, Lombard analyzes internationalization at the departmental level of an academic library. Demonstrating that college and library personnel have positive intentions when it comes to internationalization, the research presented nevertheless reveals little commitment to an intentional, holistic role in the libraries studied. Drawing on internationalization expertise and models of prominent scholars, the book argues that libraries need to be more deliberate in their internationalization efforts and collaborate with other college personnel and departments outside the library. Lombard asserts that internationalization can facilitate a better understanding of the potential for transformation of a library's mission, vision, and policy. The Internationalization of the Academic Library cuts across the fields of library science and higher education administration, ensuring that the book will appeal to researchers and students working in these disciplines. Library professionals around the world will also find much to interest them within the book.